2021
DOI: 10.3390/su13020641
|View full text |Cite
|
Sign up to set email alerts
|

Does the Household Save Water? Evidence from Behavioral Analysis

Abstract: Management of water supply in urban areas is a challenge that must be faced by water supply companies to ensure the continuity of domestic water supply to the residents in the area. Hence, this study aims to identify local people’s behavior and daily activities that led to domestic water wastage. Furthermore, the relationship between the demographic factors of the population trends in reducing water use through water savings in their daily activities or installing a home-saving water system is also undertaken.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…(double tail) was less than 0.01, confirming a significant correlation between the simulation and calculation results. Additionally, the correlation coefficient between the simulation and calculation results is 0.999437, which is close to 1, confirming an extreme correlation [35][36][37]. As shown in Table 7, the relative error between the calculated results of Equation ( 1) and those of the numerical simulation is less than 20%, indicating that the numerical model of tailing particle sedimentation established in this experiment is relatively reliable.…”
Section: Resultssupporting
confidence: 68%
“…(double tail) was less than 0.01, confirming a significant correlation between the simulation and calculation results. Additionally, the correlation coefficient between the simulation and calculation results is 0.999437, which is close to 1, confirming an extreme correlation [35][36][37]. As shown in Table 7, the relative error between the calculated results of Equation ( 1) and those of the numerical simulation is less than 20%, indicating that the numerical model of tailing particle sedimentation established in this experiment is relatively reliable.…”
Section: Resultssupporting
confidence: 68%
“…The quantity of water consumed by a household is proportional to the size of the household, and larger households tend to consume more water. 37 Given that the use of improved water comes with a cost, this might be one of the reasons why households with five or more members are more likely to use unimproved water. Similar to our results on the association of household size with sanitation, other studies have reported that the use of unimproved toilet facilities is less likely among larger households.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are similar to the results of another nationally representative study19 that used data from the 2014 Ghana DHS,18 in which households with more members were more likely to have access to improved toilet facilities but not access to improved drinking water. The quantity of water consumed by a household is proportional to the size of the household, and larger households tend to consume more water 37. Given that the use of improved water comes with a cost, this might be one of the reasons why households with five or more members are more likely to use unimproved water.…”
Section: Discussionmentioning
confidence: 99%
“…Watering plants in the early morning and late evening [51]; despite the fact that gardens are uncommon in low-income neighborhoods.…”
mentioning
confidence: 99%
“…Using collected rainwater to external uses [51] or other uses inside the home; • Using reuse water for less prestigious uses (e.g., flushing the toilet); • Invest in more efficient hydraulic devices.…”
mentioning
confidence: 99%